Sistem Monitoring dan Penjernihan Air Berdasarkan Derajat Keasaman (PH) dan Kekeruhan Pada Bak Penampungan Air Berbasis Internet of Things - Mario Orlando; Werman Kasoep (Universitas Andalas, 2020)
There are still a lot area that have not goten water from PDAM, therefore, people try to make artesian well made by themselves. Although, not all of them can afford to make their own artesian well. Therefore, governtment make a national program called Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS). Therefore, we need a technology which can detect and purify water turbidity for the water that people use everyday. People can see wether the water is decent to be consumed and if not therefore the system can pour alum automatically. The designed system in the form of conected hardware and software to monitor water quality based on turbidity and water pH through smartphone. Hardware system include microcontroller Arduino Uno, LDR sensor, pH sensor, servo motor, Sim808 modul and LED. The used softwares in this research are android aplication and firebase database. The system can save turbidity and pH data therefore, people can monitor through their smartphone and get information about level of the water. The goal of this system is to make people’s life become more easier to know the water’s condition and purify the water which will be used without going to the water tub